PENGARUH PROGRAM PERTUKARAN MAHASISWA MERDEKA DALAM MENINGKATKAN SIKAP TOLERANSI MAHASISWA FKIP UNIVERSITAS SRIWIJAYA - Helin Melinda; Kurnisar, S.Pd., M.H (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effectiveness of the Independent StudentExchange Program in increasing the tolerance attitude of FKIP students atSriwijaya University. This research uses a quantitative approach with acorrelational research design. The population in this study is all FKIP students atSriwijaya University who graduated from PMM Batch 4, totaling 33 people, takenusing non-probability sampling techniques of saturated sampling type. Thequestionnaire in this study uses a Likert scale, and the data collection techniquesused are documentation techniques and questionnaires. The data analysistechniques used are normality tests and simple linear regression tests. The resultsof the study indicate that the Independent Student Exchange Program has asignificant effect on increasing the tolerance attitude of FKIP students at SriwijayaUniversity. This is evidenced by the significance value of 0.017. This significancevalue is less than 0.05 (0.017 < 0.05) with a percentage of 16.9%. Thus, Ha isaccepted and Ho is rejected.